The making of ethnic segregation in the labor market: Evidence from a field experiment - Moa Bursell; Magnus Bygren (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
Western labor markets are typically segregated by country of birth, with immigrants often working in immigrant-typed jobs, e.g., cleaners, taxi drivers, fast-food chefs, and similar. The aim of this paper is to investigate whether employer variation in discriminatory hiring choices contributes to the maintenance of such immigrant niches by channeling immigrants and their descendants into these types of jobs. We use correspondence audit data derived from 7,051 job applications sent to job openings in 15 different occupations in the Swedish labor market between 2013 and 2019, in which names signaling the 'foreignness' of job applicants were randomly assigned to job applications with otherwise identical qualifications. Our results suggest that employers do contribute to this type of segregation. While ethnic discrimination is pervasive in the 'native' occupations in our data, it declines as the share of foreign-born individuals working in a given occupation increases, and is low or even absent in the most immigrant-dense niches. However, the pattern is gendered: it is only 'foreign'-named men who are disproportionately channeled into such niches. We conclude that variation in discriminatory employer hiring choices appears to be partly responsible for reproducing (male-dominated) immigrant niches in the labor market.
Keywords: J71; 330; discrimination; ethnicity; segregation; correspondence audit; field experiments; labor market; hiring